CRISPR‐based detection of Helicobacter pylori in stool samples. Issue 4 (11th June 2021) - Qiu, Enming; Jin, Shaoqin; Xiao, Zhuo; Chen, Qianyun; Wang, Qiaohui; Liu, Huayong; Xie, Chanfang; Chen, Chong; Li, Zhou; Han, Shuai
Abstract: Background: Noninvasive detection of Helicobacter pylori plays an important role in clinical practice. However, few noninvasive methods have been applied in epidemiological studies due to the requirement for expensive equipment and complicated processes. The aim of this study was to establish a reliable, fast, and inexpensive noninvasive method based on CRISPR‐Cas12a technology for the detection of Helicobacter pylori in stool specimens. Method: A novel detection method based on CRISPR‐Cas12a technology was established and validated with 41 stool specimens collected from Zhujiang Hospital and compared with reliable Helicobacter pylori detection assays, such as the rapid urease test and urea breath test. Result: A CRISPR‐Cas12a system‐based method was established, and its sensitivity and specificity were evaluated. Utilizing a lateral flow biosensor, the limit of detection was 5 copies/μl, and our method could successfully distinguish Helicobacter pylori from other pathogens, suggesting no cross‐reactivity with other pathogens. Furthermore, lateral flow biosensor strips were utilized to test stool specimens, which could display the detection results in an accessible way. Conclusion: Our CRISPR‐Cas12a system‐based method successfully detected Helicobacter pylori in stool specimens. It is a rapid, simple, and inexpensive method for the detection and screening of Helicobacter pylori, which makes it a very promising supplemental test. However, its sensitivity and specificity compared with those of the gold standard test still need to be examined.